Effect of Coronavirus Disease 2019 on the Psychology and Behavior of Patients on Methadone Maintenance Treatment in Wuhan, China: A Clinical Observational Study - Liu, Xuebing; Jin, Xiaohan; Zhang, Yingying; Zhang, Lin; Li, Yi; Ma, Jun (Frontiers in Psychiatry, 2021)
Methadone maintenance treatment (MMT) is a national strategy adopted for the treatment of heroin dependency in China. The sudden outbreak of coronavirus disease 2019 (COVID-19) and the resultant social isolation in Wuhan have also had a significant negative impact on local patients undertaking MMT. In this study, 76 patients on MMT from the Wuhan First Health Clinic were selected as the research objects to investigate the effect of COVID-19 on the levels of stress, anxiety, and depression, as well as the withdrawal symptoms and craving and substance use. Our results revealed that, during the outbreak, the Perceived Stress Scale (PSS) score, HAMA score, HAMD score, and craving in the included patients was significantly higher than that at the baseline and post-epidemic (p = 0.000, p = 0.000, p = 0.000, p = 0.000, respectively); the positive rate of morphine and methamphetamine urine test was significantly lower than that during the post-epidemic period (p = 0.01, p = 0.00, respectively); the amount of tobacco used during the outbreak and the post-epidemic period was significantly higher than that at the baseline (p = 0.00, p = 0.00, respectively), while the amount of alcohol consumed during the outbreak was significantly higher than at the baseline and during the post-epidemic period (p = 0.00, p = 0.00, respectively). The negative emotions aroused by the COVID-19 outbreak and the accompanying social isolation to patients on MMT are an important factor of negative reinforcement that adversely affected the patients’ craving for drugs and the consumption of legal substances. This finding suggests the need to strengthen the psychological counseling for patients on MMT during severe epidemic, actively alleviating the negative emotions, reducing the risk of substance abuse, and strengthening drug management after the epidemic to prevent the rise of substance (legal or illegal) abuse.